Pengaruh Pengalaman Belajar Metode Project-Based Learning Terhadap Minat Berwirausaha Mahasiswa Program Studi Sarjana Terhadap Kebidanan Kediri Poltekkes Kemenkes Malang - Barokah, Lia; Pratamaningyas, Susanti; Kundarti, Finta Isti; Hardjito, Koekoeh (STIKES Karya Husada Kediri, 2025)
The high number of midwifery graduates and the limited job opportunities emphasized the need to develop entrepreneurial interest through innovative educational approaches such as the project-based learning method. The purpose of the studies was to analyze the effect of project-based learning experience on the entrepreneurial interest of student. A correlational quantitative approach with a cross-sectional design was used. The sample consisted of 60 final-year students from the Applied Midwifery Study Program in Kediri, selected using simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using the spearman rank correlation test. The results showed a significant relationship between Project-Based Learning experience and entrepreneurial interest (p = 0.000; r = 0.721). The greater the students' project-based learning experience, the higher their entrepreneurial interest. Project-based learning experience had a strong and positive influence on the entrepreneurial interest of midwifery students. These results indicate that the Project-Based Learning (PjBL) method is effective in fostering students’ active, collaborative, and creative attitudes, which are essential components in developing entrepreneurial interest. This finding reinforces the evidence that project-based learning is a relevant strategy to prepare midwifery graduates to be more independent and adaptive in facing the challenges of the job market.